Public Policy Analysis and The Aspirations Of The Community In The Process Of Driving Perda - Norbertus Jegalus (Jurnal Administrasi dan Kebijakan Publik, 2023)
This study discusses the role of community participation in making "PERDA", using the Normative Political Science (Political Philosophy) approach. The main idea is that "good governance" is a concretization of the idea of democracy at the local government level. The demand for the involvement of all "stakeholders" is the demand for democracy, with the framework of thinking that the owner of the government is not the government itself but all citizens. Therefore, all policy planning and implementation are not the business of the government alone but the affairs of the whole community. Local government is required to carry out good governance in its implementation. That means the local government must be organized democratically involving three elements, namely the government bureaucracy (state), parliament (political society), and the whole society (civil society). What is new here is the role of public participation in formulating policies in the form of "procedural" and at the same time "substantial" PERDA.